Sunflower germplasm catalogue: Necessity and benefit to sunflower researchers: Sunflower germplasm catalogue: Necessity and benefit to sunflower researchers - M Y DUDHE; M SUJATHA; H P MEENA; M K GHODKE; Y G SHADAKSHARI; J RADHAMANI; K ALIVELU; R K TYAGI; A R G RANGANATHA; K S VARAPRASAD; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
The sunflower germplasm catalogue includes information on 3216 sunflower accessions maintained at ICARIIOR and NBPGR, New Delhi. The information is on 33 morphological DUS descriptors and 8 agronomic characters. The catalogue presents comprehensive and sound scientific content aiming to increase awareness about the material and their diversity.